Evaluation of Strategies to Control a Potential Outbreak of Foot-and-Mouth Disease in Sweden - Dórea, Fernanda C.; Nöremark, Maria; Widgren, Stefan; Frössling, Jenny; Boklund, Anette; Halasa, Tariq; Ståhl, Karl (Frontiers in Veterinary Science, 2017)
To minimize the potential consequences of an introduction of foot-and-mouth (FMD) disease in Europe, EU member states are required to present a contingency plan. This study used a simulation model to study potential outbreak scenarios in Sweden, and evaluate the best control strategies. The model was informed by the Swedish livestock structure using herd information from cattle, pig and small ruminant holdings in the country. The contact structure was based on animal movement data and studies investigating the movements between farms of veterinarians, service trucks and other farm visitors. All scenarios of outbreak control included depopulation of detected herds, 3 km protection and 10 km surveillance zones, movement tracing and 3 days national standstill. The effect of availability of surveillance resources, i.e. number of field veterinarians per day, and timeliness of enforcement of interventions, was assessed. With the estimated currently available resources, an FMD outbreak in Sweden is expected to be controlled (i.e. last infected herd detected) within three weeks of detection in any evaluated scenario. The density of farms in the area where the epidemic started would have little impact on the time to control the outbreak, but spread in high density areas would require more surveillance resources, compared to areas of lower farm density. The use of vaccination did not result in a reduction in the expected number of infected herds. Pre-emptive depopulation was able to reduce the number of infected herds in extreme scenarios designed to test a combination of worst-case conditions of virus introduction and spread, but at the cost of doubling the number of herds culled. This likely resulted from a combination of the small outbreaks predicted by the spread model, and the high efficacy of the basic control measures evaluated, under the conditions of the Swedish livestock industry, and considering the assumed control resources available. The results indicate that the duration and extent of FMD outbreaks could be kept limited in Sweden using the EU standard control strategy and a 3 days national standstill.